1996
DOI: 10.1177/002076409604200301
|View full text |Cite
|
Sign up to set email alerts
|

Legislating for User Involvement in the United Kingdom: Mental Health Services and the Nhs and Community Care Act 1990

Abstract: Recent legislation in the U.K., particularly the NHS and Community Care Act 1990, has encouraged the direct participation of service users in the planning and management of care services. This paper explores evidence of how the interests of service users experiencing mental distress are represented within community care services in the U.K. and the extent to which this leads to a devolution of power to those service users. The evidence is drawn from a survey of principal officers in social services departments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…15 16 We also identified reports in which patients described dissatisfaction with the process. 17 18 Several studies commented that staff involved in initiatives found the experience rewarding, 9 19 20 but others describe difficult relationships between patients and staff 21…”
Section: Resultsmentioning
confidence: 99%
“…15 16 We also identified reports in which patients described dissatisfaction with the process. 17 18 Several studies commented that staff involved in initiatives found the experience rewarding, 9 19 20 but others describe difficult relationships between patients and staff 21…”
Section: Resultsmentioning
confidence: 99%
“…In addition, among patients with caregivers, institutionalization is closely associated with caregiver exhaustion and patients' need for supervision (Hux et al, 1998). Including measures of outcome for caregivers in clinical trials is therefore important and likely to be of increasing relevance given the policy-driven moves to community-based care in the UK (Bowl, 1996) and other countries.…”
Section: Discussionmentioning
confidence: 99%
“…The emphasis on cultural change, and promoting democracy and representation, however, mirrors other work 22,23 in relation to the National Health Service and Community Care Act 1990. Iles and Sutherland 37 stress that not all members of a culture need to be compliant with proposed changes for them to come about.…”
Section: Organisational Theorymentioning
confidence: 91%
“…Barnes and Bowl,21 writing as academics, considered the development both of autonomous action by SUs and the way in which officially sponsored initiatives interacted with this and, in some cases, led to tensions between 'official' involvement initiatives and grassroots activity. Bowl,22,23 for example, found that consultation mechanisms designed to give mental health SUs a say in service planning and delivery in accordance with the 1990 provisions were little more than rubber-stamping exercises. Others have also explored the importance of collective action to enable those often regarded as incompetent to contribute to debate about services to have their say.…”
Section: Theoretical Frameworkmentioning
confidence: 99%